Mecanismo de centralização: Da insuficiência placentária à adaptação circulatória fetal - Villas-Bôas, Juliana Marques Simões [UNESP]; Maestá, Izildinha [UNESP]; Consonni, Marcos [UNESP] (FapUNIFESP (SciELO), 2008)
The application and development of obstetric Dopplervelocimetry provide a basis for the investigation of placental insuf ciency and demonstrate the dynamic behavior of fetal circulation during hypoxia. In clinical practice, assessing hemodynamics in three vascular regions involved in pregnancy, namely the uterine, umbilical and middle cerebral arteries, has become routine. Roughly, the cerebral artery expresses the balance between uterine artery oxygen supply and umbilical artery oxygen uptake. Currently, when such balance is unfavorable, the fetal cardiac reserve is investigated by assessing the venous duct. However, determining and interpreting vascular resistance indexes is not an easy task. The starting point is to know the physiopathology of placental insuf ciency and fetal circulatory adaptation through which Doppler con rmed its role in the assessment of fetal well-being.
Brain sparing effect: From placental insufficiency to fetal circulatory adaptation
Keywords: Blood circulation; Fetus; Laser-doppler flowmetry; Placental circulation; Placental insuf ciency; adaptation; brain artery; echography; female; fetus echography; human; laser Doppler flowmetry; physiology; placenta circulation; placenta insufficiency; pregnancy; review; umbilical artery; Adaptation, Physiological; Cerebral Arteries; Female; Humans; Laser-Doppler Flowmetry; Placental Circulation; Placental Insufficiency; Pregnancy; Ultrasonography, Prenatal; Umbilical Arteries